The effect of sintering temperature on potassium feldspar addition into claytan porcelain - Mohd, Norhayati (2015)
Porcelain is one of the most complex ceramic materials composed mainly of kaolin, quartz and feldspar. Its diverse applications include tableware, whiteware and insulators. This study was performed to investigate the effects of different sintering temperature on Claytan porcelain with the addition of 0wt%, 2wt%, 4wt%, 6wt%, 8wt% and 10wt% of potassium feldspar. The study was done using the slip casting. Slip added with potassium feldspar was poured into a plaster mold and then dried. The samples were sintered at temperature 800oC, 900oC, 1000oC and 1100oC with heating rate of 10oC/min and 1 hour holding time. The samples were characterised and analysed using mechanical testing, physical analysis and observation of the surface morphology by field scanning electron microscope (FESEM). The results show that the bulk density and modulus of rupture increased when the sintering temperature increased. This is because of the decrease in the percentage of apparent porosity. This result was consistent with the analysis of surface morphology. While an increase of more than 2wt% potassium feldspar would affects the physical and mechanical properties as proven from the observation of surface morphology. The result shows that the best state of physical and mechanical properties was when the sample is sintered at 1100oC with 2wt% of potassium feldspar. At this temperature and composition the value of the percentage of apparent porosity is 29.053%, bulk density 2.060g/cm3 and the modulus of rupture is 17.352MPa.